Color doppler sonographic evaluation of inter-relations between diameter, reflux and flow volume of testicular veins in varicocele - Kocakoc, E; Serhatlioglu, S; Kiris, A; Bozgeyik, Z; Ozdemir, H; Bodakci, MN (Elsevier Sci Ireland Ltd, 2003)
Objective: Reflux is in important criterion for the diagnosis of varicoccles and in the existence of reflux more than 1 s is the lower limit for the diagnosis of varicoccles. We proposed to assess the relationship of vein diameters with the incidence, duration and flow Volume of reflux using color Doppler sonography (CDS) in patients with clinically diagnosed varicoccle. Materials and methods: Forty-seven patients with varicocele (aged 16-43) were included into the study. Reflux was assessed in spectral analysis using CDS and the duration, velocity and flow volume were measured. Results: Mean duration of reflux on right side was 1.5+/-0.3 s in 14 patients, throughout the Valsalva's maneuver in eight patients and no reflux in 25 patients. Mean duration of reflux on the left side was 1.5+/-0.3 s in 25 patients, throughout the Valsalva's maneuver in 18 patients and no reflux in four patients. The incidence of reflux in the testicular veins with a diameter lower than 3 mm wits 62.3% whereas 94.4% in veins more than 3 mm in diameter. Flow volume of reflux was less than 10 ml/min in four patients and 21.7+/-24.3 ml/min in 18 patients on right side. Four patients had flow Volume of reflux less than 10 ml/min and 39 patients had 27.9+/-35.6 ml/min on the left side. Flow volume meaningfully rose with increasing in vein diameter (r = 0.83 on right; r = 0.65 on left, P < 0.011). Conclusion: Measurement of flow volume of reflux has been considered as a more valuable method with respect to presence of reflux and/or measurement of venous diameter since flow volume reflects a combination of the vein diameters, duration and velocity of reflux. (C) 2002 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: color Doppler sonography; varicoccle; reflux; flow volume; testicular vein